Diagnosis, Surgical Treatment, Recovery, and Eventual Necropsy of a Leopard (Panthera pardus) with Thyroid Carcinoma - Ashley Malmlov; Terry Campbell; Eric Monnet; Craig Miller; Becca Miceli; Colleen Duncan (Case Reports in Veterinary Medicine)
An 18-year-old, male, castrated, captive-born leopard (Panthera pardus) presented to Colorado State University’s Veterinary Teaching Hospital with a two-week history of regurgitation. Thoracic radiographs and ultrasound revealed a well-differentiated cranioventral mediastinal mass measuring 7.5 × 10 × 5.5 cm, impinging the esophagus. A sternotomy followed by mass excision was performed. The mass was diagnosed as an ectopic thyroid carcinoma. The leopard recovered from surgery with minimal complications and returned to near-normal activity levels for just under 6 months before rapidly declining. He had an acute onset of severe dyspnea and lethargy and was euthanized. On postmortem examination the tumor was found to involve the lung, liver, thyroid, parietal pleura, bronchial lymph nodes, and the internal intercostal muscles. This case report describes the history, diagnosis, surgical treatment, postoperative care, and recovery as well as the eventual decline, euthanasia, and necropsy of a leopard with thyroid carcinoma. When compared to thyroid carcinomas of domestic animals, the leopard’s disease process more closely resembles the disease process seen in domestic canines compared to domestic cats.